Analysis on Deck Ship Conversion SPOB to LCT 234 GT Using Finite Element Method - Amalia Ika Wulandari; Andi Mursid Nugraha Arifuddin; Nurul Huda (International Journal of Marine Engineering Innovation and Research, 2022)
Landing Craft Tank (LCT) is a sea transportation that serves to carry various types of cargo and heavy mining equipment and has a large size. In shipbuilding, the construction structure on the ship is not only designed to be able to accept the load from the cargo being transported but also must be able to withstand external loads caused by waves. With the modification of the Self-Propelled Oil Barge (SPOB) ship into a Landing Craft Tank (LCT), the calculation and planning process on the deck structure of the Landing Craft Tank (LCT) ship really needs to pay attention to the stress and strain strength in order to meet the safety factors that have been set in accordance with the applicable rules. This study aims to determine the maximum allowable stress value and the safety factor of the modified structure of the Landing Craft Tank (LCT) ship deck construction. The method used in this research is the finite element method. In this study uses 2 variations of the type of support "Tee Bar" and "Angle Bar". The results of this study the value of material deformation that occurs on the ship's deck with a variation of "Angle Bar" of 1.1497 mm and the value of material deformation that occurs on the deck of a ship with a variation of "Tee Bar" of 0.97269 mm. The maximum stress value acting on the ship's deck with the "Angle Bar" profile variation is 152.64 MPa and the maximum strain value is 0.00072686 mm/mm. The maximum stress value acting on the ship's deck for the "Tee Bar" profile variation is 147, 63 MPa and the maximum strain value is 0.000703 mm/mm. The value of the Safety Factor based on the criteria for the material on the ship's deck is obtained by comparing the yield stress value of the material and the maximum working stress must be greater than 1, then the deck construction with the variation of the "Angle Bar" profile is 2,326 and for the variation of the "Tee" profile type. Bar” 2,405 are categorized as safe. As for the Safety Factor based on BKI rules for the variation of the "Angle Bar" profile of 1,638 and for the variation of the "Tee Bar" profile of 1,693 it is categorized as safe. then the deck construction with the variation of the profile type "Angle Bar" is 2,326 and for the variation of the profile type "Tee Bar" 2.405 is categorized as safe. As for the Safety Factor based on BKI rules for the variation of the "Angle Bar" profile of 1,638 and for the variation of the "Tee Bar" profile of 1,693 it is categorized as safe. then the deck construction with the variation of the profile type "Angle Bar" is 2,326 and for the variation of the profile type "Tee Bar" 2.405 is categorized as safe. As for the Safety Factor based on BKI rules for the variation of the "Angle Bar" profile of 1,638 and for the variation of the "Tee Bar" profile of 1,693 it is categorized as safe.